The use of length/diameter ratio to determine the reliability of permeability data from core samples (2014)
Petroleum reservoir quality is governed by two important petrophysical parameters namely porosity and permeability. The length of test sample used for permeability measurement can affect the result. To determine the permeability of core samples, the length and cross-sectional area of the sample must be accurately measured. Hence, there should be a standard for testing in the laboratory. For every reservoir, it must be determined to know if the reservoir is permeable or not. The key factors that control permeability data are length and diameter of the core. In testing for reservoir that has not been evaluated, the sample length/diameter ratio is critical to the result that will be achieved. Therefore, it is imperative to determine a reference for testing in all laboratories. This study is conducted in order to confirm an acceptable length/diameter ratio that will serve as a guide during preparation of test samples before commencement of permeability measurement in the laboratory. The length/diameter ratio of core plugs was varied and their permeability determined experimentally using gas permeameter.